Hakemlerde özyeterlik düzeyi ve stresle başa çıkma yöntemleri arasındaki ilişkinin incelenmesi - Reçel, Elif Esma (My University, 2025)
Amaç: Bu araştırmada, hakemlerde özyeterlik düzeyi ile stresle başa çıkma yöntemleri arasındaki ilişkinin incelenmesi amaçlanmıştır. Ayrıca hakemlerde özyeterlik düzeyi ve stresle başa çıkma yöntem ve düzeylerinin bazı değişkenlere göre farklılaşıp farklılaşmadığı incelenmiştir. Gereç ve Yöntem: Bu araştırmada “ilişkisel tarama” modeli kullanılmıştır. Gençlik ve Spor Bakanlığına bağlı 8 farklı branşta görev yapan 382 hakemden oluşan örneklem grubu ile çalışılmıştır. Araştırmada veri toplama aracı olarak; araştırmacı tarafından geliştirilen “Kişisel Bilgi Formu”, hakemlerin öz yeterlik düzeylerinin tespitinde “Hakem Öz Yeterlik Ölçeği, stresle başa çıkma yöntemleri için ise “Stresle Başa Çıkma Ölçeği” kullanılmıştır. HÖYÖ ve SBÇÖ puanlarının değişkenlere göre karşılaştırılmasında “bağımsız örneklem t-testi”, “Mann-Whitney testi”, “tek yönlü ANOVA” ve “Kruskal-Wallis testi” ve puanlar arası ilişkinin tespiti için ise “Spearman Sıra Farkları Korelasyonu testi” nden faydalanılmıştır. Bulgular: HÖYÖ düzeyleri ile SBÇÖ düzeyleri arasında bir ilişki olduğu görülmüştür. Hakemlerin “öz yeterlik” düzeyleri ile “Sosyal Destek Arama” düzeyleri arasında anlamlı bir ilişkiye rastlanmamış ancak “Soruna Yönelme” ve “Sorunla Uğraşmaktan Kaçınma” düzeyleri arasında anlamlı, pozitif yönde bir ilişki olduğu görülmüştür. Kadın hakemlerin SBÇÖ düzeylerinin erkek hakemlerinkinden daha yüksek olduğu tespit edilmiştir. HÖYÖ düzeyleri yaş, branş, aktif hakemlik süreleri ve hakemlik klasmanları için farklılık göstermiştir. Sonuç: Bu araştırma ile varılan sonuçlar kapsamında hakemlerin psikolojik özelliklerinden özyeterlik ile stresle başa çıkma yöntemleri ve düzeyleri ilişkilidir.

Objective : In this study, it was aimed to examine the relationship between self-efficacy level and stress coping methods in referees. In addition, it was examined whether self-efficacy level and methods and levels of coping with stress in referees differed according to some variables. Materials and Methods : In this study, “relational survey” model was used. A sample group consisting of 382 referees working in 8 different branches affiliated to the Ministry of Youth and Sports was studied. “Personal Information Form” developed by the researcher, “Referee Self-Efficacy Scale” for determining the self-efficacy levels of referees, and “Coping with Stress Scale” for coping with stress were used as data collection tools. “Independent sample t-test”, “Mann-Whitney test’, “one-way ANOVA” and “Kruskal-Wallis test” were used to compare RSES and CSS scores according to variables and “Spearman Rank Difference Correlation test” was used to determine the relationship between scores. Results : It was observed that there was a relationship between the levels of RSES and CSS. There was no significant relationship between the referees' “self-efficacy” levels and their “Seeking Social Support” levels, but there was a significant, positive relationship between their “Problem Orientation” and “Avoiding Dealing with Problems” levels. It was found that female referees had higher levels of CSS than male referees. RSES levels differed for age, branch, duration of active refereeing and refereeing class. Conclusion : Within the scope of the results of this study, self-efficacy, which is one of the psychological characteristics of referees, and their coping methods and levels of coping with stress are related.
Investigation of the relationship between self-efficacy level and coping with stress methods in referees
Keywords: coping with stress; Futbol hakemleri; Hakem; özyeterlik; Psikolojik yönleri; Psychological aspects; Referee; self-efficacy; Soccer referees; Spor; Sports; stresle başa çıkma